Wernicke-Korsakoff syndrome secondary to cytomegalovirus encephalitis: A case report - Luis Guillermo Uribe; María Alejandra Pérez; Camilo Andrés Lara; Natalia Rueda; Javier Augusto Hernández (Biomédica, 2017)
Cytomegalovirus (CMV) is one of the opportunistic microorganisms with the highest prevalence in immunocompromised patients. Reactivation has decreased after the introduction of highly active antiretroviral therapy (HAART). Encephalitis has been reported in the coinfection as one of the most frequent presentations. We present the case of a young adult patient with HIV infection and rapid neurological deterioration due to classic clinical symptoms and signs of the Wernicke-Korsakoff syndrome, with no risk factors for thiamine deficiency, with images by nuclear magnetic resonance typical of the syndrome, and identification of cytomegalovirus in cerebrospinal fluid. The specific treatment for CMV managed to control the symptoms with neurological sequelae in progression towards improvement. This is one of the few cases reported in the literature of Wernicke syndrome secondary to cytomegalovirus encephalitis.